Pengaruh Kualitas Pelayanan dan Kepercayaan Konsumen Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Sebagai Variabel Intervening pada Jasa Bongkar Muat Petikemas PT Kaltim Kariangau Terminal - Bogie Bramanto; Eka Yudhyani; Evi Kurniasari Purwaningrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The decreasing process of loading and unloading flow means that port service users must provide extra operations to the company. In addition, this condition also shows that the quality of service and services at PT Kaltim Kariangau Terminal still needs to be improved, because the work achievements in equipment readiness show a decreasing percentage every year. The purpose of this study is to determine the effect of service quality trust on consumer satisfaction, to determine the effect of consumer satisfaction, the effect of service quality and trust on consumer loyalty, to determine the effect of service quality and customer trust on consumer loyalty through consumer satisfaction at PT Kaltim Kariangau Terminal Container Loading and Unloading Services The method used in this study is quantitative research, the analysis tool is Partial Least Square (PLS) with a population of 137 companies represented by their operational staff, so that all research populations will be used as samples. Field Work Research and Library Research). Service quality and consumer trust have a positive and significant effect on consumer satisfaction, consumer satisfaction, service quality and consumer trust have a positive and significant effect on customer loyalty, service quality and consumer trust have a positive and significant effect on customer loyalty through customer satisfaction, trust has a positive and significant effect on customer loyalty through customer satisfaction in container loading and unloading services of PT Kaltim Kariangau Terminal